Transitivity Analysis of Welcome to Sydney: A Systemic Functional Linguistics Approach on Tourism Text - Ade Tia, Dita; Syahputra, Fikry Prastya (LingPoet: Journal of Linguistics and Literary Research, 2022)
The goal of this study is to identify the different forms of transitivity processes in the tourism text "Welcome to Sydney," as well as the most common types of the process employed in the text. This study is carried out by utilizing a quantitative descriptive method and a content analysis approach. The data was collected from a tourism text with the title "Welcome to Sydney," which is located on the internet. Halliday and Matthiessen developed the theory that was applied in this study. Based on the analysis, the "Welcome to Sydney" text contains 0 (0%) clauses that indicated material process, 2 (11,76%) clauses that indicated mental process, 3 (17,77%) clauses that indicated verbal process, 8 (47,56%) clauses that indicated relational process, 0 (0%) clauses that indicated behavioral process, and 4 (23,53%) clauses that indicated existential process. As a result, it assumed that the dominating types of processes discovered in this text were relational processes. According to this study, the "Welcome to Sydney" text tries to utilize the relational process to describe and inform readers about Sydney.